Alda-1 Attenuates Lung Ischemia-Reperfusion Injury by Reducing 4-Hydroxy-2-Nonenal in Alveolar Epithelial Cells - Ding, Jie; Zhang, Quanyi; Luo, Qipeng; Ying, Yongquan; Liu, Yiwei; Li, Yinan; Wei, Wei; Yan, Fuxia; Zhang, Hao (Critical care medicine, 2016)
Excessive oxidative stress is a main cause of lung ischemia-reperfusion injury, which often results in respiratory insufficiency after open-heart surgery for a cardiopulmonary bypass. Previous studies demonstrate that the activation of aldehyde dehydrogenase-2 could significantly reduce the oxidative stress mediated by toxic aldehydes and attenuate cardiac and cerebral ischemia-reperfusion injury. However, both the involvement of aldehydes and the protective effect of the aldehyde dehydrogenase-2 agonist, Alda-1, in lung ischemia-reperfusion injury remain unknown. Prospective laboratory and animal investigation were conducted. State Key Laboratory of Cardiovascular Disease. Primary human pulmonary alveolar epithelial cells, human pulmonary microvascular endothelial cells, and Sprague-Dawley rats. A hypoxia/reoxygenation cell-culture model of human pulmonary alveolar epithelial cell, human pulmonary microvascular endothelial cell, and an isolated-perfused lung model were applied to mimic lung ischemia-reperfusion injury. We evaluated the effects of Alda-1 on aldehyde dehydrogenase-2 quantity and activity, on aldehyde levels and pulmonary protection. We have demonstrated that ischemia-reperfusion-induced pulmonary injury concomitantly induced aldehydes accumulation in human pulmonary alveolar epithelial cells and lung tissues, but not in human pulmonary microvascular endothelial cells. Moreover, Alda-1 pretreatment significantly elevated aldehyde dehydrogenase-2 activity, increased surfactant-associated protein C, and attenuated elevation of 4-hydroxy-2-nonenal, apoptosis, intercellular adhesion molecule-1, inflammatory response, and the permeability of pulmonary alveolar capillary barrier, thus alleviated injury. Our study indicates that the accumulation of 4-hydroxy-2-nonenal plays an important role in lung ischemia-reperfusion injury. Alda-1 pretreatment can attenuate lung ischemia-reperfusion injury, possibly through the activation of aldehyde dehydrogenase-2, which in turn removes 4-hydroxy-2-nonenal in human pulmonary alveolar epithelial cells. Alda-1 pretreatment has clinical implications to protect lungs during cardiopulmonary bypass.